HUBUNGAN POLA MAKAN, AKTIVITAS FISIK, DAN CITRA TUBUH DENGAN STATUS GIZI LEBIH PADA REMAJA PUTRI DI SMA NEGERI 3 TAMBUN SELATAN - Erina Rizky Damayanti, (2020)
Adolescence is a period of development and growth of physiological, psychological, and social aspects in childhood to adulthood and adolescence is prone to more nutritional problems due to an imbalance between eating intake and energy expenditure through physical activity. The dissatisfaction of the body's image is a special concern in female adolescents for weight control. This study aimed to determine the correlation between eating patterns, physical activity, and body image with overnutrition status in female adolescents at SMAN 3 South Tambun. This study uses cross sectional design with chi-square test method. The eating patterns is carried out using SQ-FFQ, physical activity is carried out using PAL and the body image is carried out using BSQ-16 and anthropometry measurements include weight and height for 58 female adolescents. The results of the analysis show that the eating patterns (p = 0,014), the physical activity (p = 0,023), and body image (p = 0,000) Have a correlation to the overnutrition status in female adolescents (p < 0.05). This shows that there was correlation between eating patterns, physical activity, and body image with overnutrition status in female adolescents at SMAN 3 South Tambun.